Immersed in Media : Telepresence Theory, Measurement & Technology - Lombard, Matthew; Biocca, Frank; Freeman, Jonathan; IJsselsteijn, Wijnand; Schaevitz, Rachel J. (Springer International Publishing : Imprint: Springer, 2015)
Highlights key research currently being undertaken within the field of telepresence, providing the most detailed account of the field to date, advancing our understanding of a fundamental property of all media - the illusion of presence; the sense of "being there" inside a virtual environment, with actual or virtual others. This collection has been put together by leading international scholars from America, Europe, and Asia. Together, they describe the state-of-the-art in presence theory, research and technology design for an advanced academic audience. Immersed in Media provides research that can help designers optimize presence for users of advanced media technologies such as virtual and augmented reality, collaborative social media, robotics, and artificial intelligence and lead us to better understand human cognition, emotion and behaviour.